Pregnancy Outcomes in Women with Endometriosis - Falconer, Henrik (Seminars in Reproductive Medicine, 2013)
The association between endometriosis and subfertility is well known and has been the object of intense research in the last decades. However, the potential association between endometriosis and adverse pregnancy outcome has not been studied until recently. The results from epidemiological studies suggest that endometriosis is associated with preterm birth, preeclampsia, antepartal hemorrhage, and an increase in cesarean delivery. These findings suggest that women with endometriosis may need special care during pregnancy. The underlying mechanisms for the observed associations are unknown, and further studies, both experimental and epidemiological, are necessary.
Keywords: endometriosis; preterm birth; pregnancy outcome